2017
DOI: 10.1002/jcu.22432
|View full text |Cite
|
Sign up to set email alerts
|

Acute diffuse thyroid swelling: A rare complication of fine‐needle aspiration

Abstract: We present a case illustrating the rare complication of acute generalized thyroid swelling shortly after sonographic-guided fine needle aspiration of a thyroid nodule. Ultrasound revealed the presence of characteristic linear hypoechoic avascular areas interspersed throughout the gland suggestive of edema. The patient was treated conservatively, with near complete normalization of the thyroid within 24 hours. Recognition of this potential complication is important, as the rapid onset of diffuse thyroid enlarge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 8 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…17 A separate study has reported the rate of blood extravasation-related complications in the range of 1.9% to 6.4%. 18 To date, 15 cases of acute thyroid swelling following an FNA procedure have been reported in the English language literature, [7][8][9][10][11][12][13][14] including the present case. The clinicopathological features of the previously reported cases are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 A separate study has reported the rate of blood extravasation-related complications in the range of 1.9% to 6.4%. 18 To date, 15 cases of acute thyroid swelling following an FNA procedure have been reported in the English language literature, [7][8][9][10][11][12][13][14] including the present case. The clinicopathological features of the previously reported cases are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…7 To the best of our knowledge, there have been only 14 cases of this complication reported in the English language literature to date. [7][8][9][10][11][12][13][14] Herein, we report a rare case of acute transient thyroid swelling, which occurred following a US-guided FNA of a thyroid nodule.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical characteristics of all the reported cases are summarized in Table 1. [4][5][6][7][8][9][10][11][12] The average age of the patients was 47 (range, 26-70) years.…”
Section: Discussionmentioning
confidence: 99%
“…(3) The heterogeneous “cracked” appearance on US could be caused by parenchymal edema 2,8,10 . (4) Rapid and spontaneous recovery does not support thyroid hematoma, which appears to be more localized in some areas and requires days to resolve 8,10 . (5) There is a possibility of the local release of some substance that is a potent endogenous vasodilator; for example, Van den Bruel et al 10 presented a case of medullary carcinoma with ATS during FNA where the calcitonin gene‐related peptide, a potent endogenous vasodilator expressed by medullary carcinoma, was the possible reason for ATS.…”
Section: Discussionmentioning
confidence: 99%